The Effect of Weight Loss and Metabolic Interventions on Recurrence After Atrial Fibrillation Ablation - Shihan Fu; Shujie Li; Xiyuan Zhang; Ruoxin Yu; Lin Sun (Journal of Clinical Medicine, 2026)
Catheter ablation is the cornerstone of rhythm control in atrial fibrillation (AF), yet recurrence remains common, and obesity is among the most consistently implicated modifiable risk factors. Weight reduction and metabolic pharmacotherapy are increasingly used in the periprocedural period, but whether they act through a shared pathway has not been systematically examined. This narrative review compares the two approaches and asks whether metabolic agents confer protection beyond weight loss itself. Three observations argue that they do not act identically. First, the benefit of weight reduction is dose-dependent yet contingent on delivery: a structured, physician-led risk-factor program reduced 12-month arrhythmia recurrence (risk ratio 0.53), whereas nurse-led care that improved guideline adherence without structured delivery did not alter the primary endpoint. Second, sodium-glucose cotransporter 2 inhibitors (SGLT2i) have been associated with reduced recurrence across BMI strata despite producing only modest weight loss; notably, a randomized trial in patients without cardiovascular or metabolic comorbidity showed no additional benefit, whereas benefit was observed in patients with type 2 diabetes and heart failure. Third, glucagon-like peptide-1 receptor agonists (GLP-1RA) achieve greater weight loss but yield inconsistent recurrence data, and Mendelian randomization suggests their cardiometabolic benefit is largely BMI-mediated, whereas that of SGLT2i is weight-independent. Together, these observations are consistent with a working hypothesis of two partly distinct atrial substrates—an obesity-related substrate responsive to weight reduction, and a metabolic-inflammatory substrate that may respond to SGLT2i predominantly when metabolic comorbidity is present. This framework is hypothesis-generating: it rests on indirect, cross-study comparisons and has not been tested by formal mediation analysis. If confirmed, it would imply that the two interventions are complementary rather than interchangeable.